Abnormal levels of seven amino neurotransmitters in depressed rat brain and determination by HPLC‐FLD. (2nd March 2017) - Cui, Ting; Qiu, Hong‐Mei; Huang, Dan; Zhou, Qi‐Xin; Fu, Xiao‐Yan; Li, Hai‐Yan; Jiang, Xin‐Hui
Abstract: The determination of amino acids with actions like neurotransmitters or modulators has been increasingly important for diagnosis in many neuropsychiatric diseases. A rapid and simple high‐performance liquid chromatography with fluorescence detection method was developed for simultaneous determination of seven amino acids: aspartate (Asp), glutamate (Glu), serine (Ser), glutamine (Gln), glycine (Gly), taurine (Tau) and γ‐aminobutyric` acid (GABA). Homoserine was used as an internal standard. The analysis was performed on a BDS column with methanol and 50 mm sodium acetate solution (pH 6.5) using a simple gradient elution. Several parameters of the developed method were validated including linearity, accuracy, precision, extraction recovery and stability, which were within the acceptable range. The method was successfully applied to determination of real samples: hippocampus and cortex in depressed rats exposed to chronically unpredictable stress in order to study if there existed differences in the seven amino acids levels between depressed rats and control. The results showed that Asp, Gly, Tau and GABA significantly decreased with increasing Gln in the hippocampus of depressed rats, compared with that of the control group, among which obviously lower level of Asp and higher level of Gln in cortex were observed. The analytical method and the results could be useful for clinical diagnosis and further insight into pathophysiological mechanism of depression.